CO₂ mitigation in road transport: Gasoline taxation and/or fuel-efficiency regulation? - Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2009)
Although gasoline taxes are widely used (nearly) efficient CO2 emission controls, additional fuel-efficiency regulation is applied e.g. in the USA and in Europe. In a simple analytical model, we specify the welfare implications of (i) gasoline taxes, (ii) of 'gas-guzzler taxes' (iii) of fuel-efficiency standards, and of combinations of the above. Both forms (ii) and (iii) of fuel-efficiency regulation turn out to produce the same suboptimally low emission rates. Combining (i) and (ii) is also distortionary, while efficiency can be secured by combining (i) and (iii). However, in the optimal mix of the latter two instruments the fuel-efficiency standard is redundant.
Keywords: D61; H21; H22; Q52; Q53; Q58; 330; CO2 emissions; road transport; fuel efficiency regulation; gasoline tax; Mineralölsteuer; Ökosteuer; Kraftstoff; Wirtschaftliche Effizienz; Regulierung; Umweltauflage; Verkehrsökologie; Wirkungsanalyse